Intelligent read-out circuit for space radiation detection - 'Umar Abdul Aziz; Siti Fauziah Toha; Rabiatuladawiah Abu Hanifah; Nurul Fadzlin Hasbullah (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In the design of the satellite system, space radiation is among the important factors that need to be taken care of as it may contribute to system failure. This research aims to design and implement an intelligent read-out circuit to detect the level of radiation. It has the capability to measure the level of radiation. The capability of the designed device to measure the level of radiation and also the type of radiation exposure are the key components to be considered in the design of the system.  In this research, the intelligent read-out circuit has been successfully designed and tested to detect the level of radiation. The results show the capability of the system to measure the level of radiation and determine the status of radiation level using both visual and sound indicators. The designed system is able to determine the level of radiation in a short time and strengthen by the danger-alert mechanism present in the system.